Elementary. The fourth season [videorecording (DVD)] - Miller, Jonny Lee; Liu, Lucy, 1968-; Hill, Jon Michael; Noble, John, 1948-; Quinn, Aidan (CBS DVD, 2016)
A contemporary take on the legendary detective Sherlock Holmes who investigates crimes in modern-day New York City as a consultant to the NYPD and is assisted by Joan Watson, a former surgeon, who is hired by Holmes' wealthy father to help keep the eccentric detective sober.